On-Time Delivery rating is highly determined by the performance of the Inventory Management.A study in the aerospace industry in Malaysia. - Khor, Wei Min; Minai, Mohd Sobri; Md Zain, Ali Yusob (2017)
This study is to examine the inventory management as the key factor in determining the performance of the Supply Chain management.To test the significant relationship between the targeted components of inventory management (IM) against one of the measurement for supply chain management (SCM) performance, the On-Time Delivery. This study will be conducted in the aerospace industry in Malaysia.This advance technology industry with little potential for success due to poor shipment performance against customer expectation. The variables of IM are stock holding, safety stock, storage policy and inventory risk are being tested against the SCM performance dimensions of on-time delivery (OTD).The quantitative research methodology is opted for this study.Data collection will be performed involving 200 potential respondents in the aerospace industry in Malaysia. This counts for 40.5% of the population in the country.The Statistical Package for the Social Sciences (SPSS) is used to assist in the analysis. The findings indicated that only three variables to be used as predictors for the SCM performance.Contrary to the initial expectation, stock holding and stock policy were found to be insignificant for the theoretical relationship in this industry.The findings also suggested the need to examine further why stock holding is not significant in this relationship of aerospace industry.Moreover, these findings can be considered as new findings and offer different contributing dimensions to the SCM performance and these should change the mindset of the top managment of most organizations that have different attributes, in particular the new high technology industry in Malaysia.